Mapping the Changes to a Health Information Service. Issue 3 (2nd July 2016) - Lindsay, J. Michael; Partee, Robert P.; Oelschlegel, Sandra; Leonard, Kelsey
ABSTRACT: This study used mapping software to assess the impact of changes made to a medical library's outreach program, comparing the pattern of consumer and patient health information requests prior to and following the change. The study accomplished this by geocoding addresses of requests to the service from two time periods, importing these into Geographic Information Software, and then plotting the data on maps. Comparing the maps showed increased request density from specific geographic areas, an expanded geographic footprint from 20 to 38 counties, and evidence that outreach strategies pursued by the medical library increased patient and community engagement.